Seismic Risk Prioritization and Retrofit Cost Evaluation of Code-Deficient RC Public Buildings in Turkey. Issue 1 (February 2015) - Sucuoğlu, Halûk; Yakut, Ahmet; Özmen, Aydan; Kubin, Joseph
A risk prioritization procedure is developed for deficient concrete public buildings within the scope of a seismic risk reduction program. The main purpose is identifying public buildings with high damage risk in a region for efficient retrofit investments. Regularity of structural systems and repeatability of deficiencies in public buildings provide opportunities for developing simple and reliable assessment procedures. The proposed procedure is based on calculating a risk index from the comparison of lateral load demand to lateral load capacity at the critical story of a building, and then prioritize the buildings in accordance with their risk index. Final decision for retrofitting is made with reference to the ratio of retrofitting cost versus demolishing and rebuilding cost. It has been shown on a sample of 70 retrofitted public buildings that the retrofitting cost ratio of deficient buildings is independent of risk level, age, height, floor area and concrete quality.